Some management lessons from Sūrah Āli-‘Imrān based on the works of Khaled and Khan - Fontaine, Rodrigue Ancelot Harvey (Kulliyyah of Economics and Management Sciences, IIUM, 2017)
This study identifies some management implications from Sūrah Āli-‘Imrān, the third sūrah of the Qur’ān by reviewing the explanations of Khaled (n.d.) and Khan (2012). The general theme of this sūrah is developing discipline in the Muslim community. A particular emphasis is placed on the process of consultation (shūrā) as a means of rebuilding trust after the battle of Uḥud. Allah emphasises that He loves the believers and that He has forgiven them for their mistakes but that they need to follow the Prophet (peace be upon him). To better understand the wisdom of this sūrah, a case study of Ford Motor is reviewed. Trust and consultation were essential to save the company from bankruptcy. Further insights from the literature on decision making and building trust are reviewed. Particular emphasis is put on the work of Collins (2001). The implications for the management education of Muslim managers are discussed.